Lipase-catalyzed transesterification of epoxidized soybean oil to prepare epoxy methyl esters - W. Liu (Grasas y Aceites, 2018)
Epoxidized soybean oil methyl esters could be efficiently prepared with the transesterification of epoxidized soybean oil (ESBO) with a lower dosage of methanol using lipase Novozym 435 as catalyst. The optimum parameters were as follows: the molar ratio of 5:1 (methanol to ESBO), 5% Novozym 435 as catalyst, at 45 °C for 14 h, with a stirring speed of 600rpm, under which the epoxidized soybean oil methyl esters (ESBOME) could be obtained at a 95.7% yield. During the enzymatic transesterification process, the oxirane oxygen values were kept unchangeable, which indicated that excellent functional group tolerance could be achieved under such mild reaction conditions. In addition, the recyclability of the immobilized enzyme Novozym 435 in this transesterification process was examined and the results showed that the biocatalyst could be reused ten times without losing any reaction activity or selectivity. And the final products of ESBOME were also identified by IR and NMR analysis. The kinetic data obtained followed the Ping-Pong Bi mechanism model (Vmax = 6.132 mol·L-1min-1, Km,S = 0,0001 mol·L-1, Km, A = 796.148 mol·L-1, Ki, A = 0,0004 mol·L-1) with competitive inhibition by methanol.